Recent Advances in NSAIDs-Induced Enteropathy Therapeutics: New Options, New Challenges - Yun Jeong Lim; Hoon Jai Chun (Gastroenterology Research and Practice)
The injurious effects of NSAIDs on the small intestine were not fully appreciated until the widespread use of capsule endoscopy. It is estimated that over two-thirds of regular NSAID users develop injury in the small intestinal injuries and that these injuries are more common than gastroduodenal mucosal injuries. Recently, chronic low-dose aspirin consumption was found to be associated with injury to the lower gut and to be a significant contributing factor in small bowel ulceration, hemorrhage, and strictures. The ability of aspirin and NSAIDs to inhibit the activities of cyclooxygenase (COX) contributes to the cytotoxicity of these drugs in the gastrointestinal tract. However, many studies found that, in the small intestine, COX-independent mechanisms are the main contributors to NSAID cytotoxicity. Bile and Gram-negative bacteria are important factors in the pathogenesis of NSAID enteropathy. Here, we focus on a promising strategy to prevent NSAID-induced small intestine injury. Selective COX-2 inhibitors, prostaglandin derivatives, mucoprotective drugs, phosphatidylcholine-NSAIDs, and probiotics have potential protective effects on NSAID enteropathy.